THE USE OF DIGITAL TECHNOLOGY IN TEACHING MATHEMATICS - Nilufar Khalikova Mirkadirovna (PEDAGOGS, 2023)
Annotation. This article explores the integration of digital technology in the field of mathematics education, examining its impact on teaching methodologies, student engagement, and overall learning outcomes. The study delves into various literature sources to analyze the existing landscape, presents the methods employed in implementing digital tools, discusses the results observed, and concludes with insights into the implications and potential future directions for digital technology in mathematics education.